A novel index for assessing the climate potential of free-running buildings based on the acceptable upper limits of thermal comfort models across China. (15th February 2023) - Huo, Xujie; Yang, Liu; Li, Danny H.W.; Zhai, Yongchao; Lou, Siwei
Highlights: A novel index is proposed to analyse quantitatively the local climate potential of free-running buildings. The summer climate potential of free-running buildings in Harbin, Beijing, Wuhan, Kunming, and Guangzhou was found to be 90%-98%, 83%-96%, 75%-88%, almost 100%, and 62%-93%, respectively. Cities in Northern China are better suited for passive cooling design due to higher summer climate potential. There is a decrease pattern in the summer climate potential across China from 1971 to 2012. Abstract: This study gathered hourly temperatures and solar radiation data from 42 years for walls in five cities within the five major climate zones across China. The long-term hourly operative temperatures in summer were determined in accordance with the ISO standard. A novel index is proposed to analyse quantitatively the local climate potential of free-running buildings. The index calculates the number of hours when the indoor operative temperature is above/below the acceptable upper limit of thermal comfort, counted in summer or throughout a year. In Harbin, Beijing, Wuhan, Kunming, and Guangzhou, the summer climate potential of free-running buildings was found to be 90 %-98 %, 83 %-96 %, 75 %-88 %, almost 100 %, and 62 %-93 %, respectively. Cities in Northern China are better suited for passive cooling design because they have a diminishing pattern of climate potential from colder climates in the north to warmer climates in the south. Additionally, positive slopes were found for the long-term shifting patterns of hour proportion from 1971 to 2012, pointing to a decrease in the summer climate potential across China. These findings have significant effects on the analyses of how buildings can adapt to and mitigate climate change and the likely changes in energy use.